The Current Situation and Development Trend of Shale Oil Exploitation Technology at Home and Abroad - Zhao, Yongrui (Scientific Journal of Technology, 2025)
This paper analyzes the global shale oil resource pattern, exploitation status and technological development. The total amount of global shale oil recoverable resources reaches 700-80 billion tons, mainly distributed in North America, China and Russia, with the United States leading production in 2023 accounting for more than 65% of the world's production in 2023, and China being the third largest resource country, with a record high in 2023. China focuses on the technological innovation of continental shale oil, and has made breakthroughs in the three national demonstration zones to form characteristic technologies such as carbon dioxide pre-fracturing. Internationally, the United States is leading in the fields of three-dimensional development and intelligent equipment, Europe focuses on environmental protection technology, and Russia is tackling ultra-deep development. There are differences between China and the United States in geology, concepts, technology, etc., and the current shale oil development is facing challenges such as low oil recovery and environmental constraints, and the future technology will develop towards low-carbon, intelligent and cost-effective. China needs to take the path of differentiated innovation and promote the transformation of industries to benefit development to achieve the national energy security goal.